The design and implementation of the re-vitalised integrated disease surveillance and response (IDSR) in Uganda, 2013-2016 - Christine Kihembo; Ben Masiira; Lydia Nakiire; Edson Katushabe; Nasan Natseri; Immaculate Nabukenya; Innocent Komakech; Charles Lukoya Okot; Francis Adatu; Issa Makumbi; Miriam Nanyunja; Solomon Fisseha Woldetsadik; et al. (BMC, 2018)
Abstract Background Uganda adopted and has been implementing the Integrated Disease Surveillance (IDSR) strategy since 2000. The goal was to build the country's capacity to detect, report promptly, and effectively respond to public health emergencies and priorities. The considerable investment into the program startup realised significant IDSR core performance. However, due to un-sustained funding from the mid-2000s onwards, these achievements were undermined. Following the adoption of the revised World Health Organization guidelines on IDSR, the Uganda Ministry of Health (MoH) in collaboration with key partners decided to revitalise IDSR and operationalise the updated IDSR guidelines in 2012. Methods Through the review of both published and unpublished national guidelines, reports and other IDSR program records in addition to an interview of key informants, we describe the design and process of IDSR revitalisation in Uganda, 2013-2016. The program aimed to enhance the districts' capacity to promptly detect, assess and effectively respond to public health emergencies. Results Through a cascaded, targeted skill-development training model, 7785 participants were trained in IDSR between 2015 and 2016. Of these, 5489(71%) were facility-based multi-disciplinary health workers, 1107 (14%) comprised the district rapid response teams and 1188 (15%) constituted the district task forces. This training was complemented by other courses for regional teams in addition to the provision of logistics to support IDSR activities. Centrally, IDSR implementation was coordinated and monitored by the MoH's national task force (NTF) on epidemics and emergencies. The NTF and in close collaboration with the WHO Country Office, mobilised resources from various partners and development initiatives. At regional and district levels, the technical and political leadership were mobilised and engaged in monitoring and overseeing program implementation. Conclusion The IDSR re-vitalization in Uganda highlights unique features that can be considered by other countries that would wish to strengthen their IDSR programs. Through a coordinated partner response, the program harnessed resources which primarily were not earmarked for IDSR to strengthen the program nation-wide. Engagement of the local district leadership helped promote ownership, foster accountability and sustainability of the program.